2014
DOI: 10.1111/mec.12738
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome population genomics reveals severe bottleneck and domestication cost in the African rice (Oryza glaberrima)

Abstract: The African cultivated rice (Oryza glaberrima) was domesticated in West Africa 3000 years ago. Although less cultivated than the Asian rice (O. sativa), O. glaberrima landraces often display interesting adaptation to rustic environment (e.g. drought). Here, using RNA-seq technology, we were able to compare more than 12,000 transcripts between 9 O. glaberrima, 10 wild O. barthii and one O. meridionalis individuals. With a synonymous nucleotide diversity πs = 0.0006 per site, O. glaberrima appears as the least g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 96 publications
6
72
0
1
Order By: Relevance
“…We then aimed to find large divergence within those sequences, and decided to check the (micro-)collinearity status of our assemblies, and found that around 25% of the genome present enough variation to lead to collinearity breakdown. As shown on Asian rice (Sakai et al 2014; Schatz et al 2014; Zhang et al 2016), we identified thus large scale variations and thus a larger pan-genomic space than what could have been expected based only on SNP data (Nabholz et al 2014; Orjuela et al 2014). Interestingly, we found around 0.6% of our scaffolds to be absent in one assembly regarding another one.…”
Section: Discussionsupporting
confidence: 54%
“…We then aimed to find large divergence within those sequences, and decided to check the (micro-)collinearity status of our assemblies, and found that around 25% of the genome present enough variation to lead to collinearity breakdown. As shown on Asian rice (Sakai et al 2014; Schatz et al 2014; Zhang et al 2016), we identified thus large scale variations and thus a larger pan-genomic space than what could have been expected based only on SNP data (Nabholz et al 2014; Orjuela et al 2014). Interestingly, we found around 0.6% of our scaffolds to be absent in one assembly regarding another one.…”
Section: Discussionsupporting
confidence: 54%
“…Previous scans of domesticated genomes have revealed an accumulation of deleterious mutations in rice (62,63), tomatoes (64), and dogs (4). This phenomenon has been termed the "cost of domestication" and is proposed to be driven by the repetitive bottlenecks associated with domestication, which reduce the efficiency of purifying selection (4).…”
Section: Resultsmentioning
confidence: 99%
“…When considering genetic monitoring and management, these approaches provide the opportunity to assess, first, the gene variant(s) behind the traits identified and the evolution of the frequency of those variants. This issue is particularly important in domestic populations, where artificial selection has resulted in accumulation of deleterious mutations (Charlier et al., ; Nabholz et al., ; Summers, Diesel, Asher, McGreevy, & Collins, ). Management of deleterious mutations may be integrated within selection and conservation schemes (see Box ).…”
Section: Components Of Genetic Erosionmentioning
confidence: 99%